Formation of a construction cluster in the format of state investment target programs - Ryzhakova, G.; Chuprina, Yu.; Gavrikov, D.; Borodavka, M. (Ways to Improve Construction Efficiency, 2019)
The article deals with the formation of management potential of the construction cluster in the part of investment and construction projects of state target programs. The article highlights the main features of the implementation of the construction cluster development program in the format of state investment programs. The model of functioning and organization of a construction cluster is proposed, the specific feature of which is different from other models of interconnection and interaction between elements of the cluster, which allows to solve a wide range of issues.